Explaining the Formation of Online News Startups in France and the United States: A Field Analysis. (6th October 2016) - Powers, Matthew; Vera Zambrano, Sandra
Abstract : This article examines the differential formation of online news startups in Toulouse, France, and Seattle, United States. While Seattle is home to many startups, in Toulouse there have been just 4—and only 1 continues publishing. Drawing on Bourdieu's field theory, we argue that amount and types of capital held by journalists in the 2 cities varied as a result of differences in journalism's position in the field of power. These differences shaped the extent of startup formation in each city and structured journalists' capacities to convert their capital into the resources needed to form startups (e.g., funding, credentials, partnerships). These findings are positioned in relation to literatures on journalism innovation and comparative media.